"Cheaper and better": Societal cost savings and budget impact of changing from systemic to intralesional pentavalent antimonials as the first-line treatment for cutaneous leishmaniasis in Bolivia. - Daniel Eid Rodríguez; Miguel San Sebastian; Anni-Maria (Public Library of Science (PLoS), 2019)
INTRODUCTION:Cutaneous leishmaniasis (CL), endemic in Bolivia, mostly affects poor people in rainforest areas. The current first-line treatment consists of systemic pentavalent antimonials (SPA) for 20 days and is paid for by the Ministry of Health (MoH). Long periods of drug shortages and a lack of safe conditions to deliver treatment are challenges to implementation. Intralesional pentavalent antimonials (ILPA) are an alternative to SPA. This study aims to compare the cost of ILPA and SPA, and to estimate the health and economic impacts of changing the first-line treatment for CL in a Bolivian endemic area. METHODS:The cost-per-patient treated was estimated for SPA and ILPA from the perspectives of the MoH and society. The quantity and unit costs of medications, staff time, transportation and loss of production were obtained through a health facility survey (N = 12), official documents and key informants. A one-way sensitivity analysis was conducted on key parameters to evaluate the robustness of the results. The annual number of patients treated and the budget impact of switching to ILPA as the first-line treatment were estimated under different scenarios of increasing treatment utilization. Costs were reported in 2017 international dollars (1 INT$ = 3.10 BOB). RESULTS:Treating CL using ILPA was associated with a cost-saving of $248 per-patient-treated from the MoH perspective, and $688 per-patient-treated from the societal perspective. Switching first-line treatment to ILPA while maintaining the current budget would allow two-and-a-half times the current number of patients to be treated. ILPA remained cost-saving compared to SPA in the sensitivity analysis. CONCLUSIONS:The results of this study support a shift to ILPA as the first-line treatment for CL in Bolivia and possibly in other South American countries.